Evaluating 36 years of fishing sustainability in a large reservoir - Luiz Guilherme dos Santos Ribas; Pitágoras Augusto Piana; Caroline Henn; Anderson Luís Maciel; Geuza Cantanhêde; Maurício Spagnolo Adames; Éder André Gubiani (Scientific Reports)
Abstract Various fishing activities are common economic practices in large hydroelectric reservoirs, such as Itaipu. Consequently, the Itaipu company has monitored artisanal commercial fishing since the formation of its reservoir. In this study, we used long-term monitoring data to evaluate the sustainability of this fishing activity in the Itaipu Reservoir, one of the largest reservoirs in the Neotropical region. Sustainability was evaluated by analyzing raw data patterns, evaluating species abundance distributions, building surplus production models, and forecasting biomass under different fishing scenarios. This evaluation spanned 36 years (1987–2022) and provided insights into 25 fish stocks. Additionally, we examined changes in stocks before and after 2000, coinciding with the construction of a fish pass and Porto Primavera Dam, a large upstream hydroelectric power plant. Our results show that, even after 40 years since the formation of the reservoir, biomass yields continue to decline, with fishing not being the primary cause, and certain stocks only being recorded after 2000. In 2022, we identified 12 fish stocks as sustainable, nine as recovering biomass, and four as overfished. We consider fishing in the Itaipu Reservoir to be currently sustainable, though concerns persist regarding the four overfished stocks and the decreasing biomass, which could pose future challenges for fishing activities in the reservoir. Additionally, the data suggests that even 40 years after the reservoir was formed, fish populations may not yet be stable in large reservoirs.